The Effectiveness of Pictorial Teaching Materials in English Language to Improve the Understanding of Mentally Retarded - Thamrin, Heriani; Sunardi, Sunardi; Supriyadi, Supriyadi (Proceeding of International Conference on Special Education in South East Asia Region, 2023)
The Effectiveness of Using Pictorial Teaching Materials in Class VII English Learning (Studies at SMPLB)" The research uses a qualitative research approach. The qualitative research approach was chosen because the research was carried out in natural conditions or described the actual situation of the Special School. The aims of this research were (1) to find out what media was used in SMPLB (2) to find out the effectiveness of using picture media in teaching English at SMPLB (3) To find out what supports and hinders the use of media images in learning English at SMPLB. To obtain these data, researchers used several instruments, namely by using observation and interview guidelines. Furthermore, the data obtained were then processed and analyzed using qualitative descriptive analysis. The results of the study show the application and effectiveness of the use of media images in learning English at SMPLB. There is a change in the motivation to learn English for mentally retarded students in Class VII SMPLB, the motivation to learn English for mentally retarded students in Class VII SMPLB is categorized as high.